Text-Based Language Teaching in the New-Normal Era to Achieve Communicative Competence: Challenges for EFL Teachers - Yulistiyanti Yulistiyanti; Sri Mulatsih; Katharina Rustipa (Script Journal: Journal of Linguistics and English Teaching, 2021)
Abstract Background: To live in this communicative era, people need to have communicative competence. The main aim of ELT is to enable the students to communicate or to produce a text. Thus, EFL teaching needs to facilitate them to achieve communicative competence so that they can participate actively in their communities. EFL teachers can utilize text-based teaching to realize this. Text-based teaching involves the use of texts, which are context bases for achieving communicative competence. This paper is a reflection, describing the teachers' common problems in implementing text-based teaching, especially under the COVID-19 pandemic. Methodology: This study is qualitative survey research to gain in-depth information about the topic of the study. The goal of this study is to describe the teachers' perception of Text-Based Approach in ELT and to describe their challenges to implement text-based online teaching. Open-ended survey questions were delivered to 15 research participants. To get a comprehensive understanding of the research participants' opinions, the researchers followed up their answers with an interview via a telephone call. Findings: The questionnaire, interview, and teachers’ self-written reflection revealed the teachers’ common problems in implementing text-based teaching, i.e. in selecting texts, in adapting or in modifying texts, in designing tasks, in overcoming students’ boredom, besides the problems of online teaching. Conclusion: The main root of the problems is the teachers' lack of knowledge of text-based approach. Thus, updating the teachers' knowledge can be one of the solutions to the problems.